Pengaruh Variasi Suhu Deodorisasi terhadap Mutu Minyak Makan Merah (Red Palm Oil) - Hanifah Khairiah; Antonius Jumadi Sihotang (Politeknik Kampar, 2024)
Red cooking oil is one of the oleofood products derived from CPO whose carotene content is maintained. Carotene is an important compound for the body because it can act as provitamin A. In addition, carotene is also a natural antioxidant for the body. The process of making RPO goes through several stages, one of which is the deodorization process. The deodorization process in making palm cooking oil is different from the deodorization in making RPO. Deodorization in making RPO is no longer intended to reduce ALB but only to improve the aroma of the oil. While deodorization at high temperatures can actually reduce the carotene content in RPO. This study was conducted by varying the deodorization temperature so that the optimal temperature was obtained to eliminate the odor in the oil but still had high carotene and the aroma was still preferred. This study was conducted in the Palm Oil Processing Engineering Laboratory by varying the deodorization temperature, namely 900C, 1200C, and 1500C with a pressure of 36 mmHg.